Development of a targeted genotyping platform for reproducible results within tetraploid and hexaploid blueberry - Clare, Shaun J.; Driskill, Mandie; Millar, Timothy R.; Chagné, David; Montanari, Sara; Thomson, Susan; Espley, Richard V.; Muñoz, Patricio; Benevenuto, Juliana; Zhao, Dongyan; Sheehan, Moira J.; Mengist, Molla F.; et al. (Frontiers in Horticulture, 2024)
Blueberry (Vaccinium spp.) is one of the most economically important berry crops worldwide. Validation of genetic mapping studies is often hindered by asynchronous marker technology. The development of a standardized genotyping platform that targets a specific set of polymorphic loci can be a practical solution to unify the scientific and breeding community toward blueberry improvement. The objective of this study was to develop and evaluate a targeted genotyping platform for cultivated blueberries that is affordable, reproducible, and sufficiently high density to warrant large-scale adoption for genomic studies. The Flex-Seq platform was developed in a two-step procedure that resulted in 22,000 loci that yielded 194,365 single nucleotide polymorphisms when assessed in a diversity set of 192 samples including cultivated and other related wild Vaccinium species. Locus recovery averaged 89.4% in the cultivated polyploid blueberry (northern highbush [NHB], southern highbush [SHB], and rabbiteye [RE]) and on average 88.8% were polymorphic. While recovery of these loci was lower in the other Vaccinium species assayed, recovery remained high and ranged between 60.8% and 70.4% depending on the taxonomic distance to the cultivated blueberry targeted in this platform. NHB had the highest mean number of variants per locus at 9.7, followed by RE with 9.1, SHB with 8.5, and a range between 7.7 and 8.5 in other species. As expected, the total number of unique-in-state haplotypes exceeded the total number of variants in the domesticated blueberries. Phylogenetic analysis using a subset of the SNPs and haplotypes mostly conformed to known relationships. The platform also offers flexibility about the number of loci, depth of sequencing for accurate dosage calling, loci and haplotype reconstruction from increased fragment length. This genotyping platform will accelerate the development and improvement of blueberry cultivars through genomic-assisted breeding tools.